Development of novel treatment with a bioabsorbable esophageal patch for benign esophageal stricture. Issue 8 (1st December 2015) - Takase, K.; Aikawa, M.; Okada, K.; Watanabe, Y.; Okamoto, K.; Sato, H.; Nonaka, K.; Yamaguchi, S.; Sakuramoto, S.; Koyama, I.; Miyazawa, M.
Summary: Using a large animal model, we examined whether circumferential stricture after esophageal endoscopic submucosal dissection (ESD) can be treated by grafting a bioabsorbable esophageal patch. Circumferential ESD was performed on the thoracic esophagus in pigs ( n = 6) to create a stricture, for which one of the following interventions was performed: (1) the stricture site was longitudinally incised, and an artificial esophageal wall (AEW) was grafted after placing a bioabsorbable stent (AEW patch group, n = 3); (2) endoscopic balloon dilation (EBD) was performed every other week after stricture development (EBD group, n = 3). In both groups, esophageal fluoroscopy was performed 8 weeks after the interventions, and the esophagus was excised for histological examination of the patched site. In the AEW patch group, esophageal fluoroscopy revealed favorable passage through the patched site. Histologically, the mucosal epithelium and lamina propria had regenerated as in the normal area. In the EBD group, the circumferential stricture site showed marked thickening, and there were hypertrophic scars associated with epithelial defects on the luminal surface. Histologically, defects of the mucosal epithelium and full-thickness proliferation of connective tissue were observed. AEW patch grafting was suggested to be a potentially novel treatment strategy for post-ESD esophageal circumferential stricture.